Understanding and managing ischemic stroke. - Barber, P; Auer, R; Buchan, A; Sutherland, G (2001)
Transient or permanent focal brain injury following acute thromboembolic occlusion develops from a complex cascade of pathophysiological events. The processes of excitotoxicity, peri-infarct depolarisation, inflammation, and apoptosis within the ischemic penumbra are proposed. While the translation of therapeutic agents from the animal models to human clinical trials have been disappointing, there remains an atmosphere of optimism as a result of the development of new diagnostic and therapeutic approaches, which include physiological, as opposed to pharmacological, intervention. This article provides an insight into the understanding of cerebral ischemia, together with current and future treatment strategies.